Manajemen Program Komunitas Belajar Sekolah untuk Peningkatan Kompetensi Pedagogik Guru - Joko Arifin; Muh Hanif (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The low pedagogical competence of teachers is the basis for this research. Efforts to improve this use the school learning community program. Research objectives: (1) describe the management of the school learning community program, (2) determine the relationship and influence of the school learning community program on pedagogical competence, (3) determine the magnitude of the increase in pedagogical competence, and (4) describe the achievement categories of the school learning community and pedagogical competence . The research was carried out from 20 to 27 April 2024 at SMP Negeri 2 Pengadegan. Qualitative and quantitative research methods were used in this research. Data collection techniques: questionnaires, observations, interviews, and documentation. Qualitative data was analyzed using the Miles and Huberman Model. Quantitative data was analyzed using tests: normality, homogeneity, product moment correlation and linear regression. Research conclusions: (1) the learning community program has been well managed through activities a) planning: team formation, goal setting, commitment making, and socialization, b) organizing: issuing a decision letter, c) implementation: delivering material and concrete PMM actions, and d) supervision: questionnaires, Google forms, and direct reflection, (2) there is a strong relationship and significant influence between the school learning community and pedagogical competence, with a correlation coefficient of 0.7274 and a determination coefficient of 52.92%, (3) Teacher pedagogical competence increased from 69.69 to 88.22, and (4) Achievement of the school learning community was in the low to very high category, while pedagogical competence was in the low to high category.